HISTOPATHOLOGICAL AND RISK FACTORS OF TISSUE LUNG CANCER IN IRAQ PATIENTS REVIEW ARTICLE - Sabreen Saleem Abd Alkreem Alsaqi (Scholar Express Journals, 2023)
The most prevalent kind of cancer, lung cancer, claims a significant number of lives every year. In a case when the cells in the body start growing out of control, it might result in cancer. Squamous cell carcinoma, adenocarcinoma, and large cell carcinoma represent the 3 main sub-types of cancer. The most prevalent kind of cancer is adenocarcinoma, which frequently affects long-term smokers. The second most prevalent cancer type is squamous cell carcinoma, which frequently affects those with a history of sun exposure or smoking. The cultural and social environment in Iraq that promotes tobacco use is the cause of the problem. Smoking is one of the leading causes of lung cancer cases and is responsible for 90% of lung cancer fatalities. Another significant environmental risk factor for lung cancer is indoor radon exposure. The chance of developing lung cancer is doubled in the cases where there is a family history of the disease. There is a higher risk when exposed to air pollution, have a history of lung disease, receive high radiation doses, or are near chemical or industrial carcinogens. More than one type of cancer was linked to mutations of TP53 tumor suppressor gene and EGFR oncogene. The EGFR is a transmembrane tyrosine kinase receptor promoting cell survival and proliferation.
Keywords: Lung cancer; Histopathological